The Predictive Value of Proportional Evaluation Based on the Metabolic Activity of Cervical Lymph Nodes on PET/CT Imaging in Patients with Larynx Cancer - Sağlampınar Karyağar, Sevda (Mol Imaging Radionucl Ther, 2020)
OBJECTIVES: We aimed to evaluate the proportional values of maximum standardized uptake value (SUV(max)) for cervical lymph nodes on (18)F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) for prediction of the presence of metastasis in patients with larynx squamous cell cancer (LSCC). METHODS: This retrospective study involved 43 patients with LSCC. All patients underwent resection of the primary tumor and neck dissection within 4 weeks after undergoing (18)F-FDG PET/CT examinations. Receiver operating characteristic (ROC) analysis was performed to evaluate the lymph node SUV(max)/primary tumor SUV(max) (SUV(max)LN/SUV(max)PT), lymph node SUV(max)/aortic SUV(max) (SUV(max)LN/SUV(max)A), and lymph node SUV(max)/liver SUV(max) (SUV(max)LN/ SUV(max)L) ratios for diagnosis of lymph node metastasis. RESULTS: SUV(max)LN/SUV(max)A, SUV(max)LN/SUV(max)L, and SUV(max)LN/SUV(max)PT rates were significantly higher in metastatic lymph nodes compared to non-metastatic nodes. ROC analysis for metastasis showed that the cut-off thresholds were 3.87 for SUV(max)LN; 1.78 for SUV(max)LN /SUV(max)A; 1.08 for SUV(max)LN/SUV(max)L; and 0.36 for SUV(max)LN/SUV(max)PT. The diagnostic sensitivity, specificity and AUC were 83.7%, 77%, 0.856 for SUV(max)LN; 79.7%, 84%, 1.78 for SUV(max)LN/SUV(max)A; 84.1%, 76%, 0.833 for SUV(max)LN/SUV(max)L; and 53.6%, 76%, 0.666 for SUV(max)LN/SUV(max)PT, respectively. CONCLUSION: SUV(max)LN/SUV(max)A, SUV(max)LN/SUV(max)L, and SUV(max)LN/SUV(max)PT ratios can be safely used for diagnosis of cervical lymph node metastasis in patients with LSCC.